Meaning in life among Muslim students - Mohamad, Mardiana; Abd. Razak, Abdul latif; Olagoke, Salami Mutiu (Elsevier, 2011)
Meaning in life as a psychological phenomenon is only understood based on the Western perspective which calls for exploring Muslims’ perception about the concept. Fifteen Muslim postgraduate students from the IIUM participated in the study. With the use of a semi-structured interview that lasted for 12-25 minutes for each participant, six themes emerged from the transcribed data. Findings reveal that Muslim students perceive that having a close relationship with God and serving His purpose helps them to perceive life to be meaningful.. Implications for the study based on cultural and existential factors and religion were also discussed.